49.4k views
4 votes
What is the solution for 4(x + 1) = 2(3x − 2)?

2 Answers

2 votes

Answer:

Explanation:

Use distributive property multiple 4(x+1) by 4 times x is 4x and 4 times 1 is 4 so it’s 4x+4=2(3x-2) than you do the same thing on the other side to get 4x+4=6x-4 than add 4 on both sides and subtract 4x on both sides to get 8=2x than divide both sides by 2 and you get x=4

User RandomWhiteTrash
by
6.0k points
0 votes

Answer:

x = 4

Explanation:

Distribute parenthesis on both sides of the equation

4x + 4 = 6x - 4 ( subtract 6x from both sides )

- 2x + 4 = - 4 ( subtract 4 from both sides )

- 2x = - 8 ( divide both sides by - 2 )

x = 4

User Sergeng
by
5.8k points